KESESUAIAN PENGASUHAN (PARENTING FIT) DI PERUSAHAAN MULTI BISNIS: STUDI KASUS KELOMPOK â€œTRANSPORTASIâ€ - Munir, Ningky (Bina Nusantara University, 2010)
A multibusiness company usually consists of a parent company or a company act as holding company and one or more subsidiaries or strategic business units. Multibusiness companies create value by influencing â€“ or parenting â€“ the businesses they owned. A good fit between a parent and its businesses will create value, a bad one will destroy it. Based on the framework developed by Goold et al. (1994) a study was conducted to assess the fit between characteristics of the parent and of its businesses in â€œTransportasiâ€ Group. Parentâ€™s characteristics consists of five groups: the parentâ€™s mental maps; the parenting structures, systems, and processes; Â functions, central services, and resources; people and skills; and decentralization contracts. Characteristics of businesses consists of three groups: business definition; parenting opportunities; and critical success factors. A qualitative case study approach from Yin (1994) was used to understand parental value-creation in â€œTransportasiâ€ Group. From this qualitative research in the case of â€œTransportasiâ€ Group, we found that there are good fit between the parent and most its businesses. Values were created by the parent through stand-alone influence, linkage influence, and corporate development approaches.Â Finally, managerial implications are discussed and brief conclusion is presented.